Investigation of the Computational Framework of Leading-Edge Erosion for Wind Turbine Blades - Hongyu Wang; Bin Chen (Energies)
Non-contact acoustic detection methods for blades have gained significant attention due to their advantages such as easy installation and immunity to mechanical noise interference. Numerical simulation investigations on the aerodynamic noise mechanism of blade erosion provide a theoretical basis for acoustic detection. However, constructing a three-dimensional erosion model remains a challenge due to the uncertainty in external natural environmental factors. This study investigates a leading-edge erosion calculation model for wind turbine blades subjected to rain erosion. A rain erosion distribution model based on the Weibull distribution of raindrop size is first constructed. Then, the airfoil modification scheme combined with the erosion distribution model is presented to calculate leading-edge erosion mass. Finally, for a sample National Renewable Energy Laboratory 5 MW wind turbine, a three-dimensional erosion model is investigated by analyzing erosion mass related to the parameter of the attack angle. The results indicate that the maximum erosion amount is presented at the pressure surface near the leading edge, and the decrease in erosion on the pressure surface is more rapid than the suction side from the leading edge to the trailing edge. With an increase in the attack angle, the erosion on the pressure side is more severe. Furthermore, a separation vortex appears at the leading edge of the airfoil under computational non-uniform erosion. For aerodynamic noise, a larger sound pressure level with significant fluctuation occurs at 400–1000 Hz.